Soil Stabilization With A Mixture Of Rice Husk Ash And Lime: A Literature Review For Road Construction Applications - Sipiq, Engriza Gino (CV. SINAR HOWUHOWU, 2025)
This study investigates the use of rice husk ash (RHA) and lime for stabilizing clayey soil, with the aim of improving its properties for road construction applications. The experimental tests, including Atterberg limits, compaction, unconfined compressive strength (UCS), cyclic wetting-drying, and California Bearing Ratio (CBR), were performed on untreated and stabilized soil samples. The results showed that the addition of RHA and lime significantly reduced the plasticity, improved the compaction characteristics, increased the strength, and enhanced the durability of the clayey soil. The optimal mixture, consisting of 10% lime and 10% rice husk ash, exhibited the highest improvement in soil properties, making it suitable for road subgrade and foundation materials. The study highlights the potential of utilizing agricultural waste, such as rice husk ash, in soil stabilization, offering a cost-effective and environmentally sustainable solution for road construction.